Laboratory results and mathematical modeling of spore surface interactions in stormwater runoff - Mikelonis, Anne M.; Ratliff, Katherine; Youn, Sungmin (Journal of contaminant hydrology, 2020)
Development of numerical models to predict stormwater-mediated transport of pathogenic spores in the environment depends on an understanding of adhesion forces that dictate detachment after rain events. Zeta potential values were measured in the laboratory for Bacillus globigii and Bacillus thuringiensis kurstaki, two common surrogates used to represent Bacillus anthracis, in synthetic baseline ultrapure water and laboratory prepared stormwater. Zeta potential curves were also determined for materials representative of urban infrastructure (concrete and asphalt). These data were used to predict the interaction energy between the spores and urban materials using Derjaguin-Landau-Verwey-Overbeek (DLVO) modeling. B. globigii and B. thuringiensis kurstaki sourced from Yakibou Inc., were found to have similar zeta potential curves, whereas spores sourced from the U.S. military's Dugway laboratory were found to diverge. In the ultrapure water, the modeling results use the laboratory data to demonstrate that the energy barriers between the spores and the urban materials were tunable through compression of the electrical double layer of the spores via changes of ionic strength and pH of the water. In the runoff water, charge neutralization dominated surface processes. The cations, metals, and natural organic matter (NOM) in the runoff water contributed to equalizing the zeta potential values for Dugway B. globigii and B. thuringiensis kurstaki, and drastically modified the surface of the concrete and asphalt. All DLVO energy curves using the runoff water were repulsive. The highest energy barrier predicted in this study was for Dugway B. globigii spores interacting with a concrete surface in runoff water, suggesting that this would be the most challenging combination to detach through water-based decontamination. •Stormwater equalizes surface charge differences between different surrogates for B. anthracis.•Surface properties of urban materials dictate spore-surface interactions in stormwater.•DLVO modeling predicted highest energy barrier between B. globigii spores and concrete.